IgG4-related gastric disease with plasma cell-rich obliterative arteritis accompanied by early-stage gastric cancer: a case report - Masayoshi Obatake; Koichi Sato; Shigehiko Yagi; Hiromi Ohtani; Katsumi Kito (Surgical Case Reports)
Abstract Background Immunoglobulin G4-related disease (IgG4-RD) is an immune-mediated inflammatory disorder that can involve multiple organs. It is characterized by IgG4-positive plasma cell-rich storiform fibrosis and obliterative phlebitis associated with a high serum IgG4 level. There are few reports of gastric IgG4-RD, especially those detected prior to systemic or other organ involvement. Case presentation: A 70-year-old man was diagnosed with type 0–IIc gastric cancer at the anterior wall of the gastric corpus by upper gastrointestinal endoscopy. In addition, a submucosal tumor (SMT) 7 mm in diameter was found at the greater curvature of the angulus. Laparoscopic distal gastrectomy with regional lymph node dissection was performed. Pathology revealed a poorly differentiated adenocarcinoma in the type 0–IIc lesion and storiform fibrosis with infiltration of a large number of IgG4-positive plasma cells in the SMT. Postoperative laboratory testing showed elevation of serum IgG4 levels; thus, we diagnosed the SMT as IgG4-RD. Intriguingly, the gastric IgG4-RD lesion demonstrated IgG4-positive plasma cell-rich arteritis as well as typical obstructive phlebitis. The patient has been followed for 2 years after surgery without recurrence of cancer, but skin lesions of IgG4-RD have appeared. Conclusion We report a rare case of IgG4-RD presenting as a gastric SMT, accompanied by early-stage gastric cancer. Our case may support a newly proposed relationship between IgG4-RD and malignancies. The gastric IgG4-RD lesion showed arteritis as well as obliterative phlebitis, potentially providing novel insight into IgG4-related vascular lesions.